From the history of the village of Gvileti - Svetlana I. Akkieva; Lejla G. Gagieva (Кавказология)
This article is devoted to the history of the village of Gvileti, located at the foot of Mount Kazbek in the modern Kazbek municipality of Georgia. The article offers numerous data on the circumstances and period of the village's founding. Based on a set of sources, the ethnic composition of the people and their changes during the nineteenth and early twentieth centuries are demonstrated, as well as the causes of these changes. The article focuses on the analysis of demographic indicators of the nineteenth century based on government statistics (desk descriptions, lists of residents, censuses). The natural mobility of the people is examined, and statistical data on the population, gender, and age composition of the inhabitants are presented. The article describes the economic situation of the population and the form of occupation and notes that the population was associated with the fund of free agricultural land. The article presents the religious composition of the population and its change, the factors that determined the migration of residents of Gwileti are noted.